A Sea Change in the Law of Contract Interpretation? - McLauchlan, David (Victoria University of Wellington Law Review, 2019)
This article challenges the recent extrajudicial argument of Sir Geoffrey Vos, Chancellor of the High Court of England and Wales, that there has been a "distinct sea change" in the law of contract interpretation as a result of the United Kingdom Supreme Court’s decisions in Rainy Sky SA v Kookmin Bank, Arnold v Britton and Wood v Capita Insurance Services Ltd. He suggests that these decisions have the effect that Lord Hoffmann’s well-known restatement of the law in Investors Compensation Scheme Ltd v West Bromwich Building Society, particularly his Lordship’s fourth and fifth principles, no longer represent the law. In his view, the position now is that a court must give the words of a contract their plain meaning except "in a most exceptional case or a case of obvious absurdity". However, Professor McLauchlan argues that Sir Geoffrey reads more into the decisions than is warranted by the Supreme Court’s reasoning and that Lord Hoffmann’s restatement has survived largely unscathed. In substance, the reasoning spelt out what was either explicit or implicit in the restatement in the first place.